School Management System - BCPams (Academic Management System): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The School Management System - BCPMAS (Academic Management System) Projectproposed to make the work of School Academic Management more efficient in Schedulingand Grade managing the student records of a school in Bestlink College of the Philippines(BCP). The Academic Management system's goal is to make the transactions easier for userslike Admin, Program heads, Strand Heads, and Dean. This system will help them manageevery transaction in the specific management more efficiently.Throughout the development process, the team saw several opportunities to create a betterand more unique system for department heads and users.Academic Management System is a Web-based system that can manage SchoolManagement, Faculty List Reports, Grade management, and Report Monitoring. Thestudents, teachers, and supporting learning activities and modalities are the primary focus ofthe BCPAMS Project.
Keywords: Computer Science; Engineering